What we know and whot we do not know about rare plants (CHORNOMORSKI BOTANICAL JOURNAL, 2010)
The system of concepts, used for the estimation of plants rarity is analyzed and the basic categories of rareness are distinguished: true, diffuse, peripheral and temporal. Lack of scientific information on ecological and coenotic connections of rare plants is shown and the necessity of complex estimation of rare plant population systems is justified.
Keywords: rare plants,forms of rarity, category of rarity.